Intrapleural streptokinase in the management of malignant multiloculated pleural effusions - Davies, C; Traill, Z; Gleeson, F; Davies, R (1999)
Objective: Pleural effusions are a frequent complication of malignancy and cause considerable morbidity from dyspnea. The drainage and control of malignant effusions relieve symptoms and maintain quality of life but these are difficult in patients with multiloculated effusions in whom drainage usually fails. This observational series reports the use of intrapleural streptokinase (IPSK) in the management of malignant multiloculated pleural effusions resistant to standard chest tube drainage. Methods: Ten consecutive patients with malignant multiloculated pleural effusions, aged 39 to 89 years, were given 250,000-IU doses of IPSK twice daily after failure to drain the effusions with a standard chest tube because of multiloculation and multiseptation, as demonstrated by CT or ultrasound scanning. Outcome was assessed by radiographic improvement and symptom control. Results: All 10 patients responded to between 500,000 and 1,500,000 IU of streptokinase. There was an increase in pleural fluid drained (mean volume ± SD; pre-IPSK, 843±690 mL; post-IPSK, 2,368±1,051 mL; p < 0.001, paired t test), and radiographic improvement was seen in all 10 patients. All subjects tolerated the instillation of streptokinase well. One subject required opiate analgesia for transient chest pain, and there were no hemorrhagic or allergic complications. One patient died of unrelated septicemia. Conclusions: This series suggests that IPSK may be useful in the drainage of malignant multiloculated pleural effusions in patients who fail to drain adequately with a standard chest tube. Malignant pleural effusions should not be considered a contraindication to IPSK.